The electric charge of black holes within galaxies - Padilla, Nelson David (2024)
We present improved estimates of the electric charge that black holes could hold when these are embedded in the ionised plasma within galaxies. We have implemented the spontaneous emission of charges of opposite sign to that of the black hole via athermal Hawking evaporation, including its dependence on black hole spin, and we have estimated the equilibrium charge that arises as this charge loss is balanced by the continuous accretion of charges from the surrounding plasma. The resulting charge can be several orders of magnitude lower than previously estimated upper limits, but it can surpass the pair production limit noted by Gibbons (1974) by a margin that increases with the amplitude of the black hole spin and the density of the plasma. We also implement a calculation for the net charge of galaxies due to their stellar black holes and to primordial black holes in the case these make up a fraction of the dark matter. We find that these charges lie within the range that would produce adequate magnetic field seeds at the onset of galaxy formation.